how to integrate (x^2 +2x +2)/ (-x^2 e^x)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to use the linearity of integral such that:

`int (x^2 +2x +2)/(-x^2 e^x) dx = int x^2/(-x^2)*e^(-x)dx - 2 int x/(x^2)e^(-x)dx - 2 int 1/(x^2)e^(-x)dx`

`int (x^2 +2x +2)/(-x^2 e^x) dx = - int e^(-x)dx - 2 int 1/x*e^(-x)dx - 2 int 1/(x^2)*e^(-x)dx`

You need to solve the integral `int 1/x*e^(-x)dx`  using parts such that:

`int udv = uv - int vdu`

`u = 1/x => du = -1/x^2 dx`

`dv = e^(-x)dx => v = -e^(-x)`

`int 1/x*e^(-x)dx = -(e^(-x))/x - int 1/x^2*e^(-x)dx`

`int (x^2 +2x +2)/(-x^2 e^x) dx = e^(-x) + 2(e^(-x))/x + 2int 1/x^2*e^(-x)dx- 2 int 1/(x^2)*e^(-x)dx`

Reducing like terms yields:

`int (x^2 +2x +2)/(-x^2 e^x) dx = e^(-x) + 2(e^(-x))/x + c`

`int (x^2 +2x +2)/(-x^2 e^x) dx = e^(-x)(1 + 2/x) + c`

Hence, evaluating the given integral yields `int (x^2 +2x +2)/(-x^2 e^x) dx = e^(-x)(1 + 2/x) + c.`

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial